Cognitive metaphors and comparisons in Udmurt riddles about bees - Tatiana R. Dushenkova (Publishing house "Sreda", 2024)
The work is devoted to the consideration of riddles about bees in the Udmurt linguistic culture. The article aims to study comparisons and metaphors, as well as analyze the image of an insect in riddles. The material was riddles reflected in special folklore publications and lexicographic sources. During the analysis, linguoculturological, semantic, etymological, and conceptual methods were used. As a result of the study, it was revealed that the bee in riddles is presented in the form of complex metaphors, comparisons and euphemisms. The bee and the hive in Udmurt culture are revealed in different categories. The hive is most often associated with a house, a pit and a syulyk (a woman's headdress). The sounds made by a bee and a bee colony are compared to the crying of a baby, the whining of a dog, or the growling of a motor. The bee itself or the bee family is associated in popular fantasy with a daughter-in-law, who is sad about parting with her parents and expecting hardships in the new family. Riddles about bees are typically compared to a huge number of people or a flock of sheep. In quantitative terms, the sound or hum of a beehive corresponds to a hundred or a thousand. Along with crying, the flight of bees from the hive is compared to sifting flour. Fairy tales also reflect the bee's ability to sting, build honeycombs, and make honey.